2011
DOI: 10.1007/s12028-011-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neurocritical Care: A Brief Report on the Survey Results of Neurosciences and Critical Care Specialists

Abstract: Broad level of support exists among the survey respondents (mostly neurologists and intensivists) for the establishment of neurological critical care units. Since neurology remains the predominant career path from which to draw neurointensivists, there may be a role for more comprehensive neurointensive care training within neurology residencies or an alternative training track for interested residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Although PNCC services are not rare, the survey did not find consensus around its perceived advantages or its shortcomings. There was more support for PNCC among surveyed p value calculated by Chi-squared analysis comparing response between two groups: respondents with and respondents without PNCC (17.5 %), though in keeping with other web-based survey results [17,18], is low and our results have a high risk of selection bias [19]. The greater number of pediatric intensivists in practice may have biased the data to represent the view of intensivists.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although PNCC services are not rare, the survey did not find consensus around its perceived advantages or its shortcomings. There was more support for PNCC among surveyed p value calculated by Chi-squared analysis comparing response between two groups: respondents with and respondents without PNCC (17.5 %), though in keeping with other web-based survey results [17,18], is low and our results have a high risk of selection bias [19]. The greater number of pediatric intensivists in practice may have biased the data to represent the view of intensivists.…”
Section: Discussionsupporting
confidence: 78%
“…In 2009, the Leapfrog Initiative funded a survey to evaluate perceptions regarding adult neurocritical care, finding broad support for the new discipline and for the establishment of adult neurocritical care units [17]. This current survey sought to pose similar questions to practitioners in pediatric critical care medicine, pediatric neurology, and pediatric neurosurgery, where both similarities and dissimilarities with the adult experience might be found.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that online surveys have lower response rates than mailed surveys is in accordance with a previous study with residents and faculty [56]. Compared to other online surveys with physicians, our response rate is acceptable (other surveys: 5% [57], 13%, [58], 72% of 68 active members of a professional society [59]). Our survey was relatively long, which may have put off potential participants.…”
Section: Limitationssupporting
confidence: 86%
“…A great variety of neurologic critical diseases were in N-ICU, not less than 50 classifications, reported by Markandaya. 13 In previous Knaus APACHE II model, neurological diseases were just classified into two categories, seizure disorder and stroke (ICH/SAH/SDH), which was not in accordance with the true composition of disease in N-ICU. In the year 2009, we found that the DCM-APACHE II model, a disease-specific formula (the neurologic diseases were classified into cerebral infarction disease, intracranial hemorrhage disease, neurologic infection disease, SNM disease, and other neurologic diseases), had more reliable accuracy in predicting mortality for neuro-critical patients in N-ICU as the discrimination of DCM-APACHE II model (AU-ROC 5 0.88) is better than that of Knaus APACHE II model (AU-ROC 5 0.81).…”
Section: Discussionmentioning
confidence: 99%